Improving Performance, Meat Quality and Muscle Fiber Microstructure of Native Indonesian Muscovy Duck Through Feed Protein and Metabolizable Energy - Tugiyanti , Elly; Yuwanta, Tri; Zuprizal; Rusman (International Journal of Poultry Science, 2013)
Tenderness is determined by the growth and size of muscle fibers, which can be arranged through the feed. The current study was designed to investigate protein and metabolic energy level on performance including meat quality and muscle fiber size of male muscovy ducks. Five protein levels and metabolic energy of feed treatments (13% and 2300 kcal/kg, 15% and 2500 kcal/kg, 17% and 2700 kcal/kg, 19% and 2900 kcal/kg, 21% and 3100 kcal/kg) and 100 male dod of muscovy ducks were administered in this research. Protein and metabolic energy level significantly affected (p<0.01) carcass weight, feed conversion ratio, abdominal fat percentage, physical meat quality and muscle fiber diameter. Feed with 21% protein and 3100 kcal/kg metabolic energy resulted in good performance (1342.60±2243.62 carcass weight, 4.00±0.64 feed conversion and 68.86±5.59% carcass percentage), physical meat quality and large muscle fiber diameter of 50.59 μm, but comparatively high abdominal fat level of 5.60±0.71.